2021
DOI: 10.1371/journal.pone.0247798
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biliary microbiota dysbiosis in extrahepatic cholangiocarcinoma

Abstract: Extrahepatic cholangiocarcinoma (CCA) accounts for 3% of digestive cancers. The role of biliary microbiota as an environment-related modulator has been scarcely investigated in CCA, and the putative impact of associated diseases has not been yet assessed. We characterized the biliary microbiota in CCA patients in order to identify a specific CCA-related dysbiosis. The biliary effluents were collected through an endoscopic retrograde pancreatic cholangiography (ERCP) examination involving 28 CCA and 47 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…The role of biliary microbiota has scarcely been investigated in CCA. However, previous studies performing 16S RNA sequencing demonstrated a significant difference of biliary microbiota composition between CCA patients and controls [162]. Initially, some authors suggested that bile fluid dysbiosis could be linked to various diseases, including biliary lithiasis.…”
Section: Gut Microbiota In Ccamentioning
confidence: 99%
See 4 more Smart Citations
“…The role of biliary microbiota has scarcely been investigated in CCA. However, previous studies performing 16S RNA sequencing demonstrated a significant difference of biliary microbiota composition between CCA patients and controls [162]. Initially, some authors suggested that bile fluid dysbiosis could be linked to various diseases, including biliary lithiasis.…”
Section: Gut Microbiota In Ccamentioning
confidence: 99%
“…Although the pathogenesis of CCA in PSC is largely unelucidated, inflammation-driven carcinogenesis concomitant with genetic and epigenetic alterations are thought to be the underlying factors [156][157][158]. However, the knowledge of predisposing risk factors is scarce and PSC-CCA development does not seem to be linked to duration and severity of PSC [159][160][161][162]. The leading hypothesis is that PSC causes multifocal strictures of the biliary tree, biliary infections, and accumulation of toxic bile acids, which results in an increased expression of adhesion and antigen-presenting molecules and inflammatory mediators.…”
Section: Psc and Cca-overviewmentioning
confidence: 99%
See 3 more Smart Citations